2020
DOI: 10.1108/jiabr-01-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

What drives Muslim Malaysian consumers’ general attitude towards religious advertising?

Abstract: Purpose Given the increased interest in the practical significance of the general attitude towards religious advertising, the purpose of this paper is to examine what influences consumers’ general attitude towards religious advertising in Malaysia. Design/methodology/approach An analytical research design was used to examine the impact of five factors (attitude towards the purpose/goal of the religious advertising [attitude institution], the quality of the message [attitude instrument], the information prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…In this sense, the religious framing might capture the viewers' attention and get them involved in the messages. As mentioned earlier, during troublesome periods when spiritual feelings are intensified, just like the Covid-19 pandemic (Bentzen, 2020;Boguszewski et al, 2020), individuals are more inclined to respond to the messages under the influence of religious teachings (Waqas, 2021). For example, the religious framing can positively affect attitudes and behaviors towards vaccination in today's pandemic conditions, reflecting a future-oriented measure to overcome a health problem.…”
Section: Religious Framing Extended-elm and Counterarguingmentioning
confidence: 96%
See 1 more Smart Citation
“…In this sense, the religious framing might capture the viewers' attention and get them involved in the messages. As mentioned earlier, during troublesome periods when spiritual feelings are intensified, just like the Covid-19 pandemic (Bentzen, 2020;Boguszewski et al, 2020), individuals are more inclined to respond to the messages under the influence of religious teachings (Waqas, 2021). For example, the religious framing can positively affect attitudes and behaviors towards vaccination in today's pandemic conditions, reflecting a future-oriented measure to overcome a health problem.…”
Section: Religious Framing Extended-elm and Counterarguingmentioning
confidence: 96%
“…Because religious individuals find notable of violating others' rightful due as a divine prohibition, use of alike sacred context in the message might lead them to appraise the information more significantly, thus to involve in the vaccination program. As an important determinant in which individuals refuge in difficult times (Bentzen, 2020;Boguszewski et al, 2020;Waqas, 2021), religious-framed communication could offer great opportunities for individuals to engage in vaccination and other health behaviors.…”
Section: Journal Of Media and Religion Studiesmentioning
confidence: 99%
“…Convergent validity is ensured when the measuring items of a construct show a level of relatedness, forcing them to make a construct (Waqas, 2021). For that, Hair et al (2016) suggested the threshold value of greater than 0.7 for factor loadings and composite reliability, whereas, for average variance extracted (AVE), the threshold value is greater than 0.5.…”
Section: Convergent Validitymentioning
confidence: 99%
“…The results reported to meet all of the aforementioned criteria and summarised in Table 3. Discriminant validity is ensured when the measuring items of a construct show a level of distinguishability with the measuring items of another construct and force them to make a respective construct (Waqas, 2021). In this study, it has been assessed by two measures.…”
Section: Convergent Validitymentioning
confidence: 99%
“…Managers responsible for promoting mutual funds believed that relevant advertising containing Islamic symbols as nudges could develop a favourable attitude towards the company's products, and customers consider such products of more value compared to competing products. Religious appeals in advertising link the products with the spiritual world by containing icons, including a crescent moon, green colour, mosque dome, arches and minaret (tower), with cultural music to give the meaning of Halalness to the product (Waqas, 2020). Customers trust religious advertising, which influences the purchasing behaviour of the consumer.…”
Section: Mutual Fund Purchase Intentionmentioning
confidence: 99%